Kontribusi LAZISNU DIY terhadap Pembangunan Berkelanjutan: Studi Program Filantropi Islam dalam Bingkai Sustainable Development Goals - Ihda Nuroini (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the contribution of the Amil Zakat, Infak, and Sedekah Institution of Nahdlatul Ulama in the Special Region of Yogyakarta (LAZISNU DIY) in supporting the achievement of the Sustainable Development Goals (SDGs) through the optimization of Islamic social fund management. The main issue examined is how the strategies, program models, and implementation carried out by LAZISNU DIY can generate tangible impacts on community empowerment across various aspects of sustainable development. This research employs a descriptive qualitative approach with data collected through in-depth interviews, field observations, and institutional documentation. The findings reveal that LAZISNU DIY’s five core program pillars education, health, economy, environment, and humanitarian-da‘wah are systematically integrated with SDG targets. Concrete contributions are evident in poverty alleviation, improving access to and quality of education, providing inclusive health services, strengthening micro, small, and medium enterprises (MSME)-based economic empowerment, and promoting participatory environmental conservation. Several innovations, such as strengthening the Zakat, Infak, and Sedekah Management Network (JPZIS), fostering strategic collaboration with pesantren and local communities, and implementing digitalization in the donation system, have significantly enhanced the effectiveness and outreach of the programs. The study affirms that LAZISNU DIY is not merely a zakat distribution institution but also a social change agent that emphasizes Islamic values and local wisdom in advancing sustainable development. Thus, LAZISNU DIY’s role is increasingly relevant in supporting the global SDG agenda while simultaneously reinforcing community social resilience at the local level. Recommendations are provided to strengthen cross-sector collaboration and establish an SDGs indicator-based evaluation system to ensure program objectives.